Risk Factors for Coronary Events After Robotic Hybrid Off-Pump Coronary Revascularization - Aleksander Dokollari; Beatrice Bacchi; Serge Sicouri; Francesco Cabrucci; Massimo Bonacchi; Danielle Spragan; Mary Ann C. Wertan; Nitin Ghorpade; Stephanie Kjelstrom; Georgia Montone; Yoshiyuki Yamashita; Basel Ramlawi; et al. (Journal of Cardiovascular Development and Disease)
Objectives: The impact of long-term complications after robotic hybrid coronary revascularization (HCR), including persistent angina, repeat revascularization, and myocardial infarction (MI), remains limited. This study aims to determine the risk factors for coronary events after robotic HCR and their time-varying effects on outcomes. Methods: We identified all consecutive patients who underwent robotic HCR at our institution. Baseline characteristics were explored as possible risk factors for angina, MI, and repeat revascularization with stents at any time during the follow-up. Results: A total of 875 patients (mean age 71.1 ± 11.1 years) were included. After a median follow-up of 3.32 years (IQR 1.18–6.34 years), angina occurred in 134 patients (15.3%), repeat revascularization with stents in 139 patients (15.8%), and MI in 36 patients (4.1%). The hazard rates for all outcomes increased with follow-up time, with a notable early rise around two years of follow-up for angina and, to a lesser extent, repeat revascularization. The risk factors were the lack of radial artery graft use, black race, diabetes, obesity, chronic obstructive pulmonary disease, low ejection fraction <50%, severe left main coronary artery stenosis (>50%), and more than three-vessel disease. Conclusions: Optimization of modifiable periprocedural risk factors may positively impact long-term prognosis in patients undergoing robotic HCR.